MAXIMUM CHELATION THERAPY RATE AFTER APPLICATION OF DIMERCAPTO- SUCCINIC ACID (DMSA) COMBINED WITH MAGNETIC TREATED WATER (MTW) AS DRINKING WATER - BASSEM M. RAAFAT (International Journal of Pharma and Bio Sciences, 2013)
Water and life are closely linked. This has been recognized throughout history by civilizations and religions and is still the case with scientists today. Water properties are found to be very effected by magnetic and electric field. The aim of this work was to study to what extend magnetic treated water can enhance the chelation rate in cases of heavy metal ions intoxications. Thirty New Zealand albino rabbits weighing between 2.5 and 3 kg were conducted to the study. Study was approved from the (The National Research Center) (NRC) ethical committee. Rabbit were subdivided into four groups. Groups I; the Control groups: Rabbits Animals received neither lead acetate nor DMSA. Groups II : Rabbits received lead acetate in the drinking water with no treatment. Group III: Rabbits Animals received lead acetate in drinking water and then treated with DMSA as a chemical chelator with using tap water as water supply drinking water. Groups IV : Rabbits Animals received lead acetate in drinking water and then treated with DMSA as chemical chelator with using magnetic drinking water treated water (MTW) as drinking water. Results showed a dramatic reduction in all body compartments lead level after administration of DMSA chelation therapy. Rabbits Animals used Magnetic drinking water MTW as drinking water recorded the lowest lead ions concentration, antioxidants activity level and hemoglobin auto-oxidation rate as compared to those received lead with no treatment. It may be preliminary concluded that, magnetic treated water usage as drinking water reduced the free radicals formation rate that in role enhance the chelation therapy process when chemical chelator is administered.